Le fratture sovracondiloidee dell’omero in età pediatrica - Boero, S.; Marengo, L.; Torchia, S.; Catena, N. (Lo Scalpello - Journal, 2018)
PEDIATRIC SUPRACONDYLAR HUMERUS FRACTURESSupracondylar humeral fracture is the most common elbow injury in pediatric population. According to themechanism of injury, these fractures can be divided in two subgroups: extension type and flexion type. Undisplacedand slightly displaced fractures can be treated conservatively. Displaced fractures require reduction followed bypercutaneous pinning. Several complications could occur in association with a supracondylar humeral fracture. Earlycomplications include neuro-vascular injury and compartment syndrome, delayed complications include cubitusvarus, joint stiffness and malunion.